Front cover: Vegan and Animal Meal Composition and Timing Influence Glucose and Lipid Related Postprandial Metabolic Profiles. Issue 5 (5th March 2019) - Draper, Colleen Fogarty; Tini, Giulia; Vassallo, Irene; Godin, Jean Philippe; Su, MingMing; Jia, Wei; Beaumont, Maurice; Moco, Sofia; Martin, Francois‐Pierre
Abstract : Mol. Nutr. Food Res . 2019, 63, 1800568 DOI:10.1002/mnfr.201800568 Flexitarian dieting is increasingly associated with health benefits. The timing of metabolic response using postprandial analysis gives a deeper understanding of how specific diet compositions influence metabolic changes in men and women, irrespective of vegan and animal diet strategies. In article number1800568 by Colleen Fogarty Draper and co‐workers, a vegan breakfast is found from fasting results to produce the same pattern of elevated branched‐chain amino acids, insulin, and glucose as an animal diet. Cover design credit: Michel Combes in collaboration with Colleen Fogarty Draper.